2020
DOI: 10.3389/ffgc.2020.581363
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Nitrogen Addition and Soil Warming Affect Conifer Seedlings’ Phenology but Have Limited Impact on Growth and Soil N Mineralization in Boreal Forests of Eastern Canada

Abstract: The increase in soil organic matter mineralization rate in boreal forests that may result from global warming is a major concern as it could release large amounts of C to the atmosphere. On the other hand, this may also release N to the soil and stimulate tree growth, which could partly offset the C losses from the soil. The long-term interaction between increased N deposition and soil warming on soil organic N mineralization and tree growth is still uncertain in the boreal zone. In this study, soil temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 96 publications
2
0
0
Order By: Relevance
“…In contrast to the prediction of our first hypothesis, experimental warming of air and soil temperature did not significantly increase seedling survival or growth. This is consistent with the results of Marty et al (2020) who found no effect of experimental warming on seedling growth, but is in contrast to Nissinen et al (2020) and Okano et al (2021) who observed a positive effect on growth, and Wright et al (2018) who found a negative effect on survival. These divergent responses can origin from different magnitudes of warming in different experiments, ranging from 0.4 • C in our experiment, over 2 • C in the experiment of Marty et al (2020) to 3.4 • C in the experiment of Wright et al (2018).…”
Section: Lack Of Seedling Response To Warmingsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to the prediction of our first hypothesis, experimental warming of air and soil temperature did not significantly increase seedling survival or growth. This is consistent with the results of Marty et al (2020) who found no effect of experimental warming on seedling growth, but is in contrast to Nissinen et al (2020) and Okano et al (2021) who observed a positive effect on growth, and Wright et al (2018) who found a negative effect on survival. These divergent responses can origin from different magnitudes of warming in different experiments, ranging from 0.4 • C in our experiment, over 2 • C in the experiment of Marty et al (2020) to 3.4 • C in the experiment of Wright et al (2018).…”
Section: Lack Of Seedling Response To Warmingsupporting
confidence: 92%
“…This is consistent with the results of Marty et al (2020) who found no effect of experimental warming on seedling growth, but is in contrast to Nissinen et al (2020) and Okano et al (2021) who observed a positive effect on growth, and Wright et al (2018) who found a negative effect on survival. These divergent responses can origin from different magnitudes of warming in different experiments, ranging from 0.4 • C in our experiment, over 2 • C in the experiment of Marty et al (2020) to 3.4 • C in the experiment of Wright et al (2018). Boreal forests are expected to experience a 1.5-4 • C increase of temperature (Gauthier et al, 2015;IPCC, 2021) suggesting that the magnitude of warming in our study was comparatively small and therefore may not have triggered a seedling response.…”
Section: Lack Of Seedling Response To Warmingsupporting
confidence: 92%